Switchable bandstop to bandpass filter using parallel-coupled resonator - Zahari, M.K. (Institute of Electrical and Electronics Engineers Inc., 2018)
A new prototype of switchable bandstop to bandpass filter was designed and fabricated by using parallel-coupled lossy resonator. The lossy resonator topology was used to partially compensate for the losses. The fundamentals of having two lossy Q resonator structures are that it exhibits a bandpass filter, where the parallel-coupled resonator is disconnected with the Î»/4 wavelength. PIN diodes are used to change the filter's response. In the experiments, the filter exhibited a high-Q bandstop response when the PIN diodes were switched 'ON' with an operating frequency of 2.4GHz, an attenuation of 75dB and return loss S11 > 20dB. The lossy bandpass filter was produced when the PIN diodes were switched 'OFF'. The theoretical analysis together with the fabrication results were presented in this paper. Â© 2017 IEEE.